Stability of solution of the Ito-Skorokhod stochastic dynamic system of random structure with external random disturbances, Markov switching and all prehistory - В. К. Ясинський; С. В. Антонюк (Науковий вісник Ужгородського університету. Серія: Математика і інформатика, 2020)
The Ito-Skorokhod stochastic dynamical system with external random disturbances, with Markov switching and all prehistory is considered in this paper. Basic definitions of stability of a strong solution for such systems are introduced and sufficient conditions for asymptotic stability in probability in general and the asymptotic mean square stability in general are received.